CLCN1 Mutations in Czech Patients with Myotonia Congenita, In Silico Analysis of Novel and Known Mutations in the Human Dimeric Skeletal Muscle Chloride Channel - Skálová, Daniela (Public Library of Science, 2013)
Myotonia congenita (MC) is a genetic disease caused by mutations in the skeletal muscle chloride channel gene (CLCN1) encoding the skeletal muscle chloride channel (ClC-1). Mutations of CLCN1 result in either autosomal dominant MC (Thomsen disease) or autosomal recessive MC (Becker disease). The ClC-1 protein is a homodimer with a separate ion pore within each monomer. Mutations causing recessive myotonia most likely affect properties of only the mutant monomer in the heterodimer, leaving the wild type monomer unaffected, while mutations causing dominant myotonia affect properties of both subunits in the heterodimer. Our study addresses two points: 1) molecular genetic diagnostics of MC by analysis of the CLCN1 gene and 2) structural analysis of mutations in the homology model of the human dimeric ClC-1 protein. In the first part, 34 different types of CLCN1 mutations were identified in 51 MC probands (14 mutations were new). In the second part, on the basis of the homology model we identified the amino acids which forming the dimer interface and those which form the Cl(-) ion pathway. In the literature, we searched for mutations of these amino acids for which functional analyses were performed to assess the correlation between localisation of a mutation and occurrence of a dominant-negative effect (corresponding to dominant MC). This revealed that both types of mutations, with and without a dominant-negative effect, are localised at the dimer interface while solely mutations without a dominant-negative effect occur inside the chloride channel. This work is complemented by structural analysis of the homology model which provides elucidation of the effects of mutations, including a description of impacts of newly detected missense mutations.